ANALYSIS OF THE EFFECTIVENESS OF CAPITAL EXPENDITURE BUDGET MANAGEMENT IN THE AGRICULTURE AND LIVESTOCK SERVICE OF CENTRAL SULAWESI PROVINCE - Nurfat Sari; Wahba; Ali Supriadi; Nur Rizkianti; Farhan Nur (Jurnal Sinar Manajemen, 2025)
To understand and analyze the management of the capital expenditure budget at the Department of Plantation and Livestock of Central Sulawesi Province. The results of this study indicate that the management of the capital expenditure budget by the Department of Plantation and Livestock of Central Sulawesi Province over the last three years, from 2019 to 2021, has been in accordance with Law Number 58 of 2005 concerning Regional Financial Management. The effectiveness of the capital expenditure budget management at the Department of Plantation and Livestock of Central Sulawesi Province over the last three years, from 2019 to 2021, fluctuated each year, a pattern which mirrored the fluctuations in its achievement against budget realization. The calculation of the capital expenditure budget effectiveness at the Department of Plantation and Livestock of Central Sulawesi Province for the Fiscal Years 2019-2021 averaged 96.57%; therefore, the budget effectiveness is considered effective as the calculation result shows a figure above 90%